Research and modelling of complex networks - Пасічник, Володимир Володимирович; Іванущак, Наталія Михайлівна (Eastern-European Journal of Enterprise Technologies, 2010)
The review of empirical and theoretical results of researches of complex networks is carried out. The attention is concentrated to dynamic and correlative properties of the Internet. There is conducted the research of topology of local computer network BW-Star & FoxNet in Chernivtsi.